Newly Released Guava Hybrids:Pusa Aarushi and Pusa Pratiksha - Goswami, Amit Kumar; Singh, Anand Kumar; Singh, S K; Thakre, Madhubala; Kumar, Chavlesh (Indian Horticulture, 2024)
Guava is one of the important fruit crops in the country and known for its high nutraceutical and medicinal value. In India, guava is cultivated almost all states except a few regions where the temperate climate prevails. Presently, India is the world’s top guava-producing country, with a growing area of 3.14 lakh hectares and 4.92 Million tonnes of production. The different guava varieties are preferred for commercial cultivation in the different guava-growing regions in the states of the country. Recently ICAR-Indian Agricultural Research Institute, New Delhi, has bred two new guava hybrids, namely Pusa Aarurushi and Pusa Pratiksha for commercial cultivation NCT region.